2022
DOI: 10.1002/bit.28195
|View full text |Cite
|
Sign up to set email alerts
|

Production of zinc protoporphyrin IX by metabolically engineered Escherichia coli

Abstract: Zinc protoporphyrin IX (ZnPPIX) has been considered as a promising red colorant for food industries as well as an anticancer drug. However, bio‐based production of ZnPPIX from a renewable carbon source has not been reported yet. In this study, a fermentation process of the metabolically engineered Escherichia coli HAEM7 strain was optimized for the high‐level production of ZnPPIX. To repurpose the HAEM7 strain that was originally developed for the production of heme into a producer of ZnPPIX, the concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Others similarly found that ZnPPIX can be overproduced by an engineered B-derived strain of E. coli under iron-poor, zinc-rich fermentation conditions . These reports indicate that heme biosynthesis in E.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Others similarly found that ZnPPIX can be overproduced by an engineered B-derived strain of E. coli under iron-poor, zinc-rich fermentation conditions . These reports indicate that heme biosynthesis in E.…”
mentioning
confidence: 85%
“…Others similarly found that ZnPPIX can be overproduced by an engineered B-derived strain of E. coli under iron-poor, zinc-rich fermentation conditions. 20 These reports indicate that heme biosynthesis in E. coli may be manipulated toward the production of non-natural metalloporphyrin cofactors. However, these cases of alternative heme metalation in E. coli depend on iron-deficient growth conditions to reduce the production of the native heme cofactor.…”
mentioning
confidence: 99%